Analisis Senyawa Metabolit Sekunder Pada Buah Black Sapote (Diospyros dygina) Atau Sawo Hitam dengan GCMS (Gas Chromatography Mass Spectometry) - Hulu, Eman Hardi Yanto; Dalimunthe, Nur Asyiah; Nasution, Syahrul (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Black Sapote (Diospyros digyna), also known as black sapote, is a tropical fruit that has high economic potential and health benefits. This study aims to identify secondary metabolite compounds found in Black Sapote pulp through maceration extraction methods and GC-MS (Gas Chromatography-Mass Spectrometry) analysis. Samples were extracted using 96% ethanol solvent and analyzed qualitatively and quantitatively. Phytochemical screening results showed that only terpenoid compounds were detected, while flavonoids and steroids were not found. GC-MS analysis identified five derivatives of terpenoid compounds, with cumulative levels of 21.04%, consisting of esters and sesquiterpenes. These ingredients show important bioactivity potentials, such as antimicrobial, antioxidant, and anti-inflammatory properties. These findings indicate that Black Sapote has the potential to be developed as a natural raw material in functional food products, herbal cosmetics, and pharmaceuticals. The lack of local research related to the bioactive content of this fruit opens up opportunities for further research for exploration and utilization in the development of tropical biological resource-based industries.